Identification and characterization of LEA gene family in physic nut and functional analysis of JcLEA1 under drought stress - Tang, Yuehui; Wang, Xiaohui; Wang, Shujing; Li, Xuechun; Bao, Xinxin; Xu, Siqiong; Liu, Dafei; Zhang, Wenxia; Jiao, Chenyu (Frontiers in Plant Science, 2026)
IntroductionLate Embryogenesis Abundant (LEA) proteins are highly hydrophilic, glycine-rich proteins that accumulate during late seed ripening and play critical roles in abiotic stress responses. However, only a limited number of LEA genes have been functionally characterized in the drought-tolerant species physic nut, and systematic investigations of their characteristics and transcriptional dynamics remain unexplored.Methods and resultsIn this study, we identified 24 LEA genes (JcLEAs) in physic nut, which were systematically categorized into eight evolutionary subgroups (LEA1 to LEA6, DHN, SMP) through comparative phylogenetic clustering with homologs from rice and Arabidopsis. Among the 24 JcLEA genes, most were predominantly expressed in seeds, with notably elevated transcript levels during the late seed maturation stage. RNA-seq data revealed that 13 JcLEA genes were responsive to one or more abiotic stress conditions (drought or salinity) in root tissues at multiple time points. Subcellular localization experiments in Arabidopsis protoplasts confirmed nuclear localization of JcLEA1, and transgenic Arabidopsis plants overexpressing JcLEA1 exhibited enhanced drought resilience compared to wild-type, as indicated by reduced relative electrolyte leakage and MDA content, elevated proline accumulation and betaine content, and enhanced superoxide dismutase activity under drought conditions. Further analysis of transgenic plants overexpressing JcLEA1 subjected to drought stress confirmed the functional role of JcLEA genes in drought tolerance.DiscussionThis study provides the first in-depth genomic characterization of the LEA gene family members in physic nut, complemented by functional investigations that advance our understanding of its role in abiotic stress adaptation. Our findings offer a foundation for molecular breeding strategies to improve drought tolerance in bioenergy crops, particularly physic nut.